2023
DOI: 10.1101/2023.01.11.523688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional signatures of heroin intake and seeking throughout the brain reward circuit

Abstract: Opioid use disorder (OUD) looms as one of the most severe medical crises currently facing society. More effective therapeutics for OUD requires in-depth understanding of molecular changes supporting drug-taking and relapse. Recent efforts have helped advance these aims, but studies have been limited in number and scope. Here, we develop a brain reward circuit-wide atlas of opioid-induced transcriptional regulation by combining RNA sequencing (RNAseq) and heroin self-administration in male mice modeling multipl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…S5a) ( 27 ). Consistent with previous transcriptomic profiling by RNA-seq in response to drugs of abuse ( 28, 29 ), this approach reliably captured canonical marker genes temporally associated with the addicted state (Fig. 5b, c and Fig.…”
Section: Resultssupporting
confidence: 83%
“…S5a) ( 27 ). Consistent with previous transcriptomic profiling by RNA-seq in response to drugs of abuse ( 28, 29 ), this approach reliably captured canonical marker genes temporally associated with the addicted state (Fig. 5b, c and Fig.…”
Section: Resultssupporting
confidence: 83%
“…Using gene ontology analysis, we found that this hub gene cluster enriched for biological processes related to extracellular matrix (ECM) maintenance and associated collagen biology. This finding was particularly interesting given our recent work profiling transcriptional regulation in a mouse model of OUD, as well as recent findings in postmortem NAc from patients with OUD, both of which implicate an important role for ECM dysregulation in supporting opioid addiction pathology (11,12,30). Nearly all genes in this cluster were associated with module 3 (see sunburst plots in Figure 2), a large gene network containing nearly 5700 genes (Supp Fig 2B).…”
Section: Resultsmentioning
confidence: 70%
“…Mice were treated with cocaine (20 mg/kg) or morphine (10 mg/kg), at doses known to cause strong rewarding effects in mice (21), or with saline, for 10-15 days, followed by 30 days of long-term withdrawal. The 30 d timepoint was chosen to coincide with a period of abstinence associated with high levels of drug craving that promotes relapse (22), and has been linked to dynamic transcriptional regulation within the NAc for both cocaine and opioids (9,11). At the 30 d time point, animals received a challenge injection of either saline, cocaine, or morphine in the homecage and were euthanized 1h later, at which point the NAc was dissected and flash frozen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limma-Voom with covariate selection (covariates included TMT plex, sex, age, PMI, and peptide expression) was used to detect differentially expressed (DE) proteins between unaffected subjects and subjects with OUD in homogenate and synaptosome protein fractions for each brain region [23]. Proteins were considered DE if both p<0.05 and log2 fold-change (logFC) were greater than or equal to ±0.26 (20% change in protein expression), as previously used [3,33,34]. Over-representation pathway analyses were completed using clusterProfiler [35] and ReactomePA [36] for DE proteins in homogenates and synaptosomes.…”
Section: Data Processingmentioning
confidence: 99%